Dual electrolyte additives of potassium hexafluorophosphate and tris (trimethylsilyl) phosphite for anode-free lithium metal batteries. (1st September 2019) - Hagos, Teklay Mezgebe; Berhe, Gebregziabher Brhane; Hagos, Tesfaye Teka; Bezabh, Hailemariam Kassa; Abrha, Ljalem Hadush; Beyene, Tamene Tadesse; Huang, Chen-Jui; Yang, Yaw-Wen; Su, Wei-Nien; Dai, Hongjie; Hwang, Bing-Joe
Abstract: Potassium hexafluorophosphate and tris (trimethylsilyl) phosphite are applied as electrolyte additives to enhance electrochemical performance of an anode-free lithium metal battery (AFLMB) based on a Cu‖NMC cell configuration. The synergistic effect of the dual additives has been investigated using a commercial carbonate electrolyte (1 M LiPF6 -EC/DEC (1:1 vol%)). Herein, we report that an electrolyte with dual additive of 2 wt% KPF6 - 2 vol% TMSP significantly improves the charge/discharge capacity, average coulombic efficiency and retention capacity of a Cu‖NMC cell configuration. An AFLMB cell with 2 wt% KPF6 - 2 vol% TMSP additives retained 48% of its initial capacity at the 20 th cycle, while the reference cell with the commercial electrolyte in the absence of additives reached only 14%. The enhanced performance using the prepared electrolyte is attributed to the self-healing electrostatic shielding (SHES) effect of KPF6 to prevent dendrite growth and the removal of hydrofluoric acid (HF) produced from the commercial LiPF6 carbonate electrolytes by the reaction of phosphorus pentafluoride (PF5 ) with water using TMSP. This study provides a broader vision in developing functional electrolyte additives for an anode-free lithium metal battery. Graphical abstract: Image 1